CHAPTER 7 REACTION PATH MODELLING OF GEOLOGICAL CO2 SEQUESTRATION - (:unkn) unknown (My University, 2006)
In this chapter we will see how to predict the course of chemical reactions occurring during the geological disposal of CO 2, building on the thermodynamic and kinetic grounds that were reviewed in previous chapters.